Design and Build a Web Service for Financial Technology Dashboard at PT. Mitra Kasih Perkasa with React JS - Muljanto, Yehuda Joy; Sanjaya, Ridwan; Widiantoro, Albertus Dwiyoga (Journal of Business and Technology, 2023)
PT Mitra Kasih Perkasa or MKP is a financial technology or fintech company, as well as a system integrator. MKP processes thousands, even millions, of financial transaction data every day, requiring efficient data management through the use of a dashboard. Information from the dashboard is used to monitor business processes and improve company performance. This research focuses on the development of efficient and effective web services for financial technology dashboards, integrating attractive and user-friendly user interfaces (UI/UX). Additionally, this research will discuss how to access web services using React JS, a popular JavaScript framework for responsive user interface development. The research will also outline the steps in building a financial technology dashboard that can help PT. Mitra Kasih Perkasa efficiently and effectively manage financial information using modern and innovative React JS technology.